Identity and mechanisms of alkane-oxidizing metalloenzymes from deep-sea hydrothermal vents - Austin, Rachel N.; Bertrand, Erin M.; Groves, John T.; Vetriani, Costantino; Keddis, Ramaydalis (Frontiers in Microbiology, 2013)
Six aerobic alkanotrophs (organism that can metabolize alkanes as their sole carbon source) isolated from deep-sea hydrothermal vents were characterized using the radical clock substrate norcarane to determine the metalloenzyme and reaction mechanism used to oxidize alkanes. The organisms studied were Alcanivorax sp. strains EPR7 and MAR14, Marinobacter sp. strain EPR21, Nocardioides sp. strains EPR26w, EPR28w, and Parvibaculum hydrocarbonoclasticum strain EPR92. Each organism was able to grow on n-alkanes as the sole carbon source and therefore must express genes encoding an alkane-oxidizing enzyme. Results from the oxidation of the radical-clock diagnostic substrate norcarane demonstrated that five of the six organisms (EPR7, MAR14, EPR21, EPR26w, and EPR28w) used an alkane hydroxylase functionally similar to AlkB to catalyze the oxidation of medium-chain alkanes, while the sixth organism (EPR92) used an alkane-oxidizing cytochrome P450 (CYP)-like protein to catalyze the oxidation. DNA sequencing indicated that EPR7 and EPR21 possess genes encoding AlkB proteins, while sequencing results from EPR92 confirmed the presence of a gene encoding CYP-like alkane hydroxylase, consistent with the results from the norcarane experiments.